Glioblastoma following Hemorrhagic Stroke: A Case Report - Kevin Kevin; Zulham Yamamoto; Bayu Dewanto (Faculty of Medicine Universitas Padjadjaran, 2021)
Objective: To report a glioblastoma (GBM) case preceded by a hemorrhagic stroke.Methods: This case reported a 53-year-old male presenting at at Murni Teguh Memorial Hospital, Medan, Indonesia, with a chief complaint of an altered mental state. The condition had been worsened for two weeks. On anamnesis, he was identified to have experienced intracerebral hemorrhage in January 2020. A follow-up head computed tomography scan was conducted in September 2020, showing a normal condition of the brain. Other oncogenic risk factors were not found. Due to convulsion in October 2020, the patient underwent a magnetic resonance imaging examination showing a cystic right temporoparietooccipital lesion and cerebral edema. Craniotomy tumor removal surgery was performed while the tumor was further examined for histopathological findings. The tumor was diagnosed as glioblastoma with microvascular proliferation and palisading necrosis.Results: There was some associations between hemorrhagic stroke and glioblastoma development.Conclusion: GBM preceded by hemorrhagic stroke is a rare case that can be diagnosed thoroughly by complete clinical and adjunct examinations.